Dissociation between running economy and running performance in elite Kenyan distance runners - Mooses, M.; Mooses, K.; Haile, D. W.; Durussel, J.; Kaasik, P.; Pitsiladis, Y. P. (Journal of Sports Sciences, 2015)
The purpose of this study was to investigate the relationship between running economy (RE) and performance in a homogenous group of competitive Kenyan distance runners. Maximal aerobic capacity (VO2max) (68.8 ± 3.8 ml·kg-1·min-1) was determined on a motorised treadmill in 32 Kenyan (25.3 ± 5.0 years; IAAF performance score: 993 ± 77 p) distance runners. Leg anthropometry was assessed and moment arm of the Achilles tendon determined. While Achilles moment arm was associated with better RE (r2 = 0.30, P = 0.003) and upper leg length, total leg length and total leg length to body height ratio were correlated with running performance (r = 0.42, P = 0.025; r = 0.40, P = 0.030 and r = 0.38, P = 0.043, respectively), RE and maximal time on treadmill (tmax) were not associated with running performance (r = -0.01, P = 0.965; r = 0.27; P = 0.189, respectively) in competitive Kenyan distance runners. The dissociation between RE and running performance in this homogenous group of runners would suggest that RE can be compensated by other factors to maintain high performance levels and is in line with the idea that RE is only one of many factors explaining elite running performance.